Recognition of Regional Water Table Patterns for Estimating Recharge Rates in Shallow Aquifers. Issue 3 (6th August 2018) - Gilmore, Troy E.; Zlotnik, Vitaly; Johnson, Mason
Abstract: We propose a new method for groundwater recharge rate estimation in regions with stream‐aquifer interactions, at a linear scale on the order of 10 km and more. The method is based on visual identification and quantification of classically recognized water table contour patterns. Simple quantitative analysis of these patterns can be done manually from measurements on a map, or from more complex GIS data extraction and curve fitting. Recharge rate is then estimated from the groundwater table contour parameters, streambed gradients, and aquifer transmissivity using an analytical model for groundwater flow between parallel perennial streams. Recharge estimates were obtained in three regions (areas of 1500, 2200, and 3300 km 2 ) using available water table maps produced by different methods at different times in the area of High Plains Aquifer in Nebraska. One region is located in the largely undeveloped Nebraska Sand Hills area, while the other two regions are located at a transition zone from Sand Hills to loess‐covered area and include areas where groundwater is used for irrigation. Obtained recharge rates are consistent with other independent estimates. The approach is useful and robust diagnostic tool for preliminary estimates of recharge rates, evaluation of the quality of groundwater table maps, identification of priority areas for further aquifer characterization and expansion of groundwater monitoring networks prior to using more detailed methods. Abstract : Article impact statement : A new, simple approach for estimating groundwater recharge from groundwater table contours by recognizing and quantifying their patterns.